Peran Penggunaan Digital Marketing Bagi Karyawan Di PT Pupuk Sriwidjaja Palembang - Oktarina, Hani; Sartika, Dewi (CV. ITTC INDONESIA, 2024)
Promotion is one of the methods that must be carried out by PT Pusri in product marketing activities. With promotions, PT Pusri can convey information regarding quality, price, brand and other information. Promotions can also be carried out to persuade, invite and convince consumers to want to buy the products offered. This research aims to determine the role of digital marketing for PT Pupuk Sriwidjaja employees. This research uses a qualitative descriptive method using interview techniques with PT Pupuk Sriwidjaja employees as the selected respondents. The results of this research show that digital marketing has become very important in the current technological era because of the shift in interest from conventional to digital. Even though PT Pupuk Sriwidjaja Palembang still uses conventional sales through kiosks and distributors, the influence of digital marketing is significant, especially in promotions.